Effect of Weather on Vehicles Speed (Case Study at KM23 FT050) - Omar, Noorliyana; Siti Fadzilah Kasno; Nurul Adila Jablan; Asmah Ibrahim; Felix Ling Ngee Leh; Jason Ling Ji Chung; Pang Jun Wen; Dillion Dampa; Low Jia Zheng; Kelvin Pang Jia Hao; Isham Ismail; Basil David Daniel; et al. (Recent Trends in Civil Engineering and Built Environment, 2025)
Statistical methods are utilized in this research to understand vehicle speed on KM 23 FT050, based on rainy and sunny weather. The data was collected on the speed of 100 vehicles that were present on the roads on the rainy and sunny days which included cars, motorcycles and trucks. Descriptive statistics such as mean, median, and standard deviation were calculated to analyze the speed variations among different vehicle types. Hypothesis testing confirmed that vehicles travel faster on sunny days, with a significant difference in speed between the two weather conditions. Furthermore, ANOVA tests showed that while speeds were roughly the same for all vehicle types in sunny weather, they varied significantly for different vehicle types in rainy conditions. The research draws particular attention on the possible effects of weather on driving speeds and implications in managing traffic on Jalan Kluang in a way that improves road safety.